Role of immediate recurrent laryngeal nerve reconstruction in surgery for thyroid cancers with fixed vocal cords. Issue 3 (20th December 2016) - Iwaki, Shinobu; Maeda, Tatsuyoshi; Saito, Miki; Otsuki, Naoki; Takahashi, Miki; Wakui, Emi; Shinomiya, Hirotaka; Morimoto, Koichi; Inoue, Hiroyuki; Masuoka, Hiroo; Miyauchi, Akira; Nibu, Ken‐ichi
Abstract: Background: Quality of voice after immediate recurrent laryngeal nerve (RLN) reconstruction in thyroid cancers has not been thoroughly studied. Methods: Thirteen patients with fixed vocal cords (fixed vocal cord group) and 8 patients with intact or impaired mobile vocal cords (mobile vocal cord group) who had immediate RLN reconstruction simultaneously with total thyroidectomy, and patients who had arytenoid adduction and thyroplasty for vocal cord paralysis caused by previous surgery (arytenoid adduction thyroplasty group) were enrolled in this study. Results: Preoperative phonation efficiency index was significantly lower ( p = .008) in the fixed vocal cord group than in the mobile vocal cord group. One year after surgery, all voice parameters of the patients in the fixed vocal cord group had improved, compared with their preoperative data. The fixed vocal cord group had attained satisfactory voice qualities equivalent to those of the mobile vocal cord group in terms of various voice parameters. Conclusion: The present results support the idea that immediate RLN reconstruction at the time of surgery for thyroid cancers may spare the need for subsequent arytenoid adduction thyroplasty even in the patients with preoperatively fixed vocal cords. © 2016 Wiley Periodicals, Inc. Head Neck 39: 427–431, 2017